Portal to address agricultural information needs of banana farmers in Embu County - Ireri, Evelyn Wanjiru (Strathmore University, 2013)
Information and Communication Technologies (ICTs) are important tools to use in agriculture today. This is more so because ICTs can make significant contribution in increasing efficiency, productivity and sustainabiIity of smallscale farmers. The greatest challenge is that despite many initiatives Agricultural knowledge and information has not been tapped and content availed to farmers in an all inclusive format. Currently the available websites only provide information which is of very little value to the farmer since it does not cover the whole agricultural value chain. The design of this research was action in that it tried to understand the banana farmers' agricultural information needs and challenges that farmers face while using ICTs, interviews were conducted to banana farmers in Embu county. This information was intended to aid the researcher in developing an appropriate tool (portal) which could contain all the information a farmer is interested in throughout the agricultural value chain. The developed portal contains information from production, to value addition and marketing which is the final stage of the agricultural value chain. However, the research recommends that the agricultural extension offices should be fully equipped with computers and internet to facilitate the extension officers to be able to train the farmers on how to acquire this information through the internet using their phones or available information hubs. Findings also suggest the need for policy makers and even private sector to invest in making access to ICT tools by farmers easier.
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Information Technology
Keywords: Agricultural information; Agriculture; Information needs; Farming; Banana farming; Embu County